Soil erodibility mapping using three approaches in the Tangiers province –Northern Morocco - Hamza Iaaich; Rachid Moussadek; Bouamar Baghdad; Rachid Mrabet; Ahmed Douaik; Derradji Abdelkrim; Abdelhak Bouabdli (International Soil and Water Conservation Research, 2016)
Soil erodibility is a key factor in assessing soil loss rates. In fact, soil loss is the most occurring land degradation form in Morocco, affecting rural and urban vulnerable areas. This work deals with large scale mapping of soil erodibility using three mapping approaches: (i) the CORINE approach developed for Europe by the JRC; (ii) the UNEP/FAO approach developed within the frame of the United Nations Environmental Program for the Mediterranean area; (iii) the Universal Soil Loss Equation (USLE) K factor. Our study zone is the province of Tangiers, North-West of Morocco. For each approach, we mapped and analyzed different erodibility factors in terms of parent material, topography and soil attributes. The thematic maps were then integrated using a Geographic Information System to elaborate a soil erodibility map for each of the three approaches. Finally, the validity of each approach was checked in the field, focusing on highly eroded areas, by confronting the estimated soil erodibility and the erosion state as observed in the field. We used three statistical indicators for validation: overall accuracy, weighted Kappa factor and omission/commission errors. We found that the UNEP/FAO approach, based principally on lithofacies and topography as mapping inputs, is the most adapted for the case of our study zone, followed by the CORINE approach. The USLE K factor underestimated the soil erodibility, especially for highly eroded areas.